Thymic cyst as a differential diagnosis of a lateral cervical mass: case report and review of literature - Goncalves, Ines C.; Ventura, Nuno; Valente, Tania; Ferreira, Gonçalo; Coelho, Maria I.; Inacio, Ana; Cunha, Fernanda; Santos, Miguel C. (International Surgery Journal, 2020)
Thymic cysts are a rare cause of benign neck mass in adults and are usually diagnosed after surgery. Their prevalence is less than 1% of all cervical masses, and they are generally noted in the first decade. We report a case of a 34 year old female with a lateral cervical mass, describing ultrasound and CT features, intraoperative findings and histopathology. Thymic cysts are uncommon lesions causing neck swelling, often misdiagnosed preoperatively and should be included in the differential diagnosis of cervical cystic masses.